Effectiveness Application of Interactive Learning Media on Creative Thinking - Maulidya, Ayu Ningrum; Ridwan, Mochamad (Media Ilmu Keolahragaan Indonesia, 2021)
This study aims to determine the effectiveness of the application of interactive learning media on creative thinking in physical education sport and health subjects. This study uses a pre-experimental design using a one group pretest-posttest design. The sample taken in class X OTKP 2 at SMKN 2 Buduran Sidoarjo totaling 38 students. For data analysis using SPSS 25 which consists of descriptive analysis, normality test, homogeneity test, andpaired sample t test. The results obtained from the pretest and posttest in class X OTKP 2 students at SMKN 2 Buduran Sidorjo there is a difference in value or an increase in value where the value comes from before being given treatment and after being given treatment.